Rational Design of MXene/1T‐2H MoS2‐C Nanohybrids for High‐Performance Lithium–Sulfur Batteries. (30th March 2018) - Zhang, Yelong; Mu, Zijie; Yang, Chao; Xu, Zhikun; Zhang, Shan; Zhang, Xiaoyan; Li, Yingjie; Lai, Jianping; Sun, Zhonghui; Yang, Yong; Chao, Yuguang; Li, Chunji; et al.
Abstract: Despite high‐energy density and low cost of the lithium–sulfur (Li–S) batteries, their commercial success is greatly impeded by their severe capacity decay during long‐term cycling caused by polysulfide shuttling. Herein, a new phase engineering strategy is demonstrated for making MXene/1T‐2H MoS2 ‐C nanohybrids for boosting the performance of Li–S batteries in terms of capacity, rate ability, and stability. It is found that the plentiful positively charged S‐vacancy defects created on MXene/1T‐2H MoS2 ‐C, proved by high‐resolution transmission electron microscopy and electron paramagnetic resonance, can serve as strong adsorption and activation sites for polar polysulfide intermediates, accelerate redox reactions, and prevent the dissolution of polysulfides. As a consequence, the novel MXene/1T‐2H MoS2 ‐C‐S cathode delivers a high initial capacity of 1194.7 mAh g −1 at 0.1 C, a high level of capacity retention of 799.3 mAh g −1 after 300 cycles at 0.5 C, and reliable operation in soft‐package batteries. The present MXene/1T‐2H MoS2 ‐C becomes among the best cathode materials for Li–S batteries. Abstract : Phase engineered MXene/1T‐2H MoS2 ‐C with plentiful S‐vacancy defects is highly effective for trapping polysulfide intermediates and accelerating redox kinetics, leading to the enhanced lithium–sulfur batteries.